2012
DOI: 10.1093/scan/nss145
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation modulates anticipatory brain activity that predicts emotional memory encoding in women

Abstract: It has been shown that the effectiveness with which unpleasant events are encoded into memory is related to brain activity set in train before the events. Here, we assessed whether encoding-related activity before an aversive event can be modulated by emotion regulation. Electrical brain activity was recorded from the scalps of healthy women while they performed an incidental encoding task on randomly intermixed unpleasant and neutral visual scenes. A cue presented 1.5 s before each picture indicated the upcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Most likely, informative cues already triggered an emotion allowing participants to anticipate what they would experience in response to the target. This possibility accords with existing evidence on cued affective responding (Kolassa et al, 2005; Kopp and Altmann, 2005; Miltner et al, 2005; Michalowski et al, 2009, 2014) and on the relation between LPP amplitude and emotion (Yang et al, 2012; Herbert et al, 2013; Langeslag and van Strien, 2013; Sarlo et al, 2013; Galli et al, 2014). …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most likely, informative cues already triggered an emotion allowing participants to anticipate what they would experience in response to the target. This possibility accords with existing evidence on cued affective responding (Kolassa et al, 2005; Kopp and Altmann, 2005; Miltner et al, 2005; Michalowski et al, 2009, 2014) and on the relation between LPP amplitude and emotion (Yang et al, 2012; Herbert et al, 2013; Langeslag and van Strien, 2013; Sarlo et al, 2013; Galli et al, 2014). …”
Section: Discussionsupporting
confidence: 91%
“…Spider phobics, as well as control participants, responded with greater LPPs to unpleasant and spider pictures as compared to neutral pictures and this effect was preceded by an analogous response to cues. Importantly, there is evidence that the LPP enhancement to both cues and targets can be dampened by emotion regulation (Herbert et al, 2013; Langeslag and van Strien, 2013; Galli et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies often use a cue-event paradigm to manipulate different categories of cues (e.g., Onoda et al, 2006Onoda et al, , 2007Onoda et al, , 2008Sarinopoulos et al, 2010;Grupe and Nitschke, 2011;Staudinger et al, 2011;Gole et al, 2012;Lin et al, 2012Lin et al, , 2014aLin et al, ,b, 2015aLin et al, ,d, 2017bLin et al, , 2018Yang et al, 2012;Aue et al, 2013;Gruber et al, 2013;Galli et al, 2014;Dieterich et al, 2016Dieterich et al, , 2017Qiao et al, 2018). In this paradigm, expectancy cues are presented before emotional events.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, several functional magnetic resonance imaging (fMRI) and ERP studies found that anticipation of emotional pictures was relevant to their later recognition ( Mackiewicz et al, 2006 ; Galli et al, 2011 , 2014 ). In terms of fMRI studies, for example, the activation in the bilateral dorsal amygdala and the anterior hippocampus during anticipation of negative pictures was positively correlated to the later recognition performance of the pictures ( Mackiewicz et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%